2017
DOI: 10.3390/ijerph14101126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Physical Inactivity during Leisure-Time and Commuting among Beneficiaries of Government Welfare Assistance in Poland

Abstract: Physical activity (PA) has well-documented health benefits helping to prevent development of non-communicable diseases. The aim of the study was to examine the prevalence and factors associated with physical inactivity during leisure-time (LTPA) and commuting (CPA) among adult social assistance beneficiaries in Piotrkowski district. The studied sample consisted of 1817 respondents. Over 73% of the study population did not meet the recommended levels of LTPA. Fifty two % of the respondents had none leisure-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Physical activity may also be affected by social inequalities. The prevalence of leisure-time physical inactivity among the beneficiaries of the welfare group was 1.5 times higher than in the general Polish population [ 33 ]. Biernat and Buchholtz’s examination, which included 1260 low-physically active adult Poles (age between 15 and 69 years), showed that lack of physical activity was especially prevalent in individuals living in rural areas or town dwellers, and was often associated with poor educational level and restrained labor market opportunities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity may also be affected by social inequalities. The prevalence of leisure-time physical inactivity among the beneficiaries of the welfare group was 1.5 times higher than in the general Polish population [ 33 ]. Biernat and Buchholtz’s examination, which included 1260 low-physically active adult Poles (age between 15 and 69 years), showed that lack of physical activity was especially prevalent in individuals living in rural areas or town dwellers, and was often associated with poor educational level and restrained labor market opportunities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely important to get to know a dietary behavior and determinants of quality of the diet among disadvantaged groups well, because in almost all the countries, the rates of death and poorer self-assessments of health have been substantially higher in groups with a low SES than in those with a higher SES [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis only 26% of the participants followed the recommendations for LTPA. An in-depth analysis focused on a LTPA and its correlates in our study population has been published previously [26]. This indicates that the men had a higher risk of inactivity during LTPA compared to the women.…”
Section: Discussionmentioning
confidence: 61%
“…Characteristics of the examined region, methodology, and the study sample have been published elsewhere [24][25][26]. Briefly, this cross-sectional study that covered beneficiaries of government welfare assistance was performed between October 2015 and February 2016 among residents of Piotrkowski district aged 18-59 years.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation